Battered women continue living in abusive relationships in Pakistan. - Yusra Saleem; Komal . (International Journal on Women Empowerment, 2022)
Cultural practices, societal views, and customs all significantly impact the mental health of women in Pakistan. Religious and ethnic tensions, attitudes that dehumanize women, extended family structures, and the role in-laws play in women's daily life are major issues and stressors. Such actions have severely marginalized Pakistani women, which has had a negative psychological impact. Men can now control women by using violence against them, which has become one of the acceptable methods for doing so. Still, Pakistani women are generally better off than their counterparts when compared to other South Asian nations. No one hypothesis can categorically foresee this tendency on the part of battered women because the problem is little understood and rarely discussed. A review of the domestic violence was conducted to determine the most important factors that forecast a woman's likelihood of staying in or leaving an abusive relationship.